Carving the Cosmos: Lilian Silburn and Discontinuism - Erika Natlia, (Revista de Filosofía, 2024)
In this article, I explore the role of the body in Indian thought through the lens of Lilian Silburn’s works, focusing on the idea of carving the cosmos, namely of somatic performances that have cosmological relevance. First, I delve into her biography, to study, subsequently, her analysis of ancient Vedic philosophy, the Brāhmaṇa, the Upanişad, and Buddhism. In this manner, I touch upon a series of conceptual developments, trying to understand the constant tensions between the discontinuous and the continuous, the non-arranged and the arranged, the multiple and the One, and finally between eternalism and nihilism. I conclude by examining the way Buddhism has of resolving these tensions in the nonsubstantial theory of Karman.